Assessment of the Use of Steel Slag and/or Air Pollution Control Devices Dust in theManufacturing of Fly Ash Bricks/Blocks - Sharma, Shivang (My University, 2015)
In today’s era, all energy planners are aiming to increase the use of oil, gas, nuclear and renewable energy sources to meet the electricity need of India, but till now the major source of electricity generation is coal-based thermal power plants and they will continue to rule till next few decades too. The major problem with coal-based thermal power plant is the disposal of fly ash produced as the waste product form the power plant. Similarly, steel slag & air pollution control devices (APCD) dust are the industrial waste with high polluting tendencies. In past, fly ash was treated as the waste product as well as a source of air and water pollution, but in the recent past, it has been considered as resourceful material in different sectors, especially in construction sector. Steel slag & APCD dust also possess similar properties as that of conventional natural aggregates and can be used as filler in fly ash bricks/blocks. In the recent studies, the properties of fly ash & steel slag revealed that their properties are comparable with natural aggregates. The properties of concrete incorporated with steel slag shows better results when compared to conventional concrete. The use of steel slag and APCD dust as a filler in fly ash bricks is yet to be explored. The present proposal aims at the assessment of use of steel melting furnace slag/APCD dust as filler in the manufacture of fly ash bricks and the evaluation of the properties of synthesized bricks/blocks as well as its associated environmental impacts. In the present study, effect of the replacement of conventional aggregates with different proportions of fly ash, steel slag and APCD dust in fly ash brick/blocks of size 230x110x75mm/300x200x150mm was evaluated in terms of water absorption and compressive strength test, as per Indian Standard Code IS-3495 (Part- I & II):1976. With the variation of fly ash from 35-70% & steel slag from 21-45%, better results were obtained for C-10 (fly ash-70%, steel slag-21% & cement- 9%). The compressive strength of 11.21 N/mm2 and water absorption 18.51% were observed for this composition. APCD dust was also varied from 5-20% but due to its very fine size, it was unable to bond strongly enough with rest of the mixture, resulting in higher water absorption rate of 24.53%. The variation of steel slag and fly ash in blocks showed good compressive strength. The composition C-13 (fly ash 45%, steel slag 45% & cement 10%) gave the good results for both compressive strength 8.37 N/mm2 and water absorption 17.68%. In the investigation of the effect of pH on bricks/blocks, pH of water used in absorption test was varied from pH 5.0-9.0. The results were insignificant on the compressive strength or the water absorption with the change in pH and even during the physical examination of bricks after water absorption test with different values of pH, the condition of bricks were good. The effluent from the water absorption was also tested for the presence of heavy metals (Fe, Pb& Zn) and the results showed that the metals were under permissible range and can be discharged in the environment. The results depicted that the use of steel slag and APCD dust as a filler in fly ash bricks/blocks proved beneficial for construction purposes as they are also cost effective and environmental friendly materials.
MT, SEE
Keywords: Seel Slag; Flyash bricks; Properties; SEE